Corporate Diplomacy: How Multinational Corporations Gain Organizational Legitimacy A Neo-Institutional Public Relations Perspective - Marschlich, Sarah (Organisationskommunikation, 2022)
This Open-Access book investigates corporate diplomacy as a legitimation strategy of multinational companies in the United Arab Emirates. The author applies a neo-institutional public relations perspective, according to which societal expectations significantly shape corporate diplomacy communication. Using a multi-method research design, the author shows how corporate diplomacy is used in the host country, what role local media coverage and relationship management fulfill, and what effects corporate diplomacy has on corporate legitimacy in the host country community, i.e., UAE residents. The findings provide substantial insights into how multinational corporations seek legitimacy through corporate diplomacy and demonstrate how these efforts and the legitimation of corporations are affected by the media and the host country's public.